Rehabilitation of Severe Impairment in Motor Function after Stroke: Suggestions for Harnessing the Potentials of Mirror Neurons and the Mentalizing Systems to Stimulate Recovery - Auwal Abdullahi; Thomson W. L. Wong; Shamay S. M. Ng (Brain Sciences, 2022)
Rehabilitation of severe impairment in motor function following stroke is very challenging. This is because one of the driving forces for recovery of motor function is tasks practice, something this category of patients cannot voluntarily perform. However, it has now been shown that tasks practice can equally be carried out cognitively and through observation of another person’s practice, using techniques known as mental practice and tasks observation, respectively. Mental practice and tasks observation are believed to activate networks of neurons in the brain known as mirror neurons and mentalizing systems to induce recovery. The effectiveness of these techniques has, however, limited evidence at the moment. One possible explanation for this could be the nature of the protocols of these techniques, especially as regards to the intensity of practice. This article proposes ways the potentials of the mirror neurons and mentalizing systems can be harnessed to optimize recovery of severe impairment in motor function using mental practice and tasks observation. The article suggests, among other ways, protocols where tasks observation or mirror therapy are carried out first, and are then followed by mental practice, increasing the number of times the tasks are observed or mentalized, observation of significant others performing the tasks and mental practice of very familiar tasks.